Cloud Enterprise Resource Planning Software Design for Healthcare Account Receivables Billing & CashTransactions - Thejas Prasad (North American Journal of Engineering Research, 2021)
As global multinational companies adopt digital transformation, cloud-native enterprise resource planning applications become a critical part of their architecture and roadmap. Modern Enterprise Resource Planning applications and reporting solutions are developed using cloud native architecture that comes with a lot of limitations in them out of the box functionalities with the seeded applications which may not directly resolve the real-world problems that exists in the healthcare industry in recording and reporting the transactions which are of complex nature. This paper will discuss on howto build an effective solution on handling the different types of use cases in the health care sector for Accounts Receivables transactions and account the transactions in an optimized way for financial reporting